Economic volatility and returns to education in Venezuela : 1992-2002 - Sakellariou, Christos N., 20./21. Jh. 20./21. Jh (Policy research working paper, 2004)
"Preliminary evidence suggests that the rates of return to education in Venezuela have been declining since the 1970s. Patrinos and Sakellariou rigorously estimate the returns to education in Venezuela for the period 1992-2002 and link them to earlier available estimates from the 1980s. They use consistent cross-sections from the Encuesta de Hogares por Muestro to document falling returns to schooling and educational levels until the mid-1990s, followed by increasing returns thereafter. The authors use quantile regression analysis to provide further insight into the within skill group changes in returns over time. This paper--a product of the Education Sector Unit, Latin America and the Caribbean Region--is part of a larger effort in the region to estimate the labor market outcomes of education"--World Bank web site